Faster smooth muscle cell coverage in ultrathin-strut drug-eluting stent leads to earlier re-endothelialization - Hahn, Dongwoo; Lee, Donghoon; Hyun, Woonggyu; Cho, Yunnie; Yoon, Chang-Hwan; Jeon, Ki-Hyun; Kang, Si-Hyuck; Youn, Tae-Jin; Chae, In-Ho (Frontiers in Bioengineering and Biotechnology, 2023)
Background: Ultrathin-strut drug-eluting stent (DES) has shown better clinical results than thin- or thick-strut DES. We investigated if the re-endothelialization was different among three types of DES: ultrathin-strut abluminal polymer-coated Sirolimus-eluting stent (SES), thin-strut circumferential polymer-coated Everolimus-eluting stent (EES), and thick-strut polymer-free Biolimus-eluting stent (BES) to gain insight on the effect of stent design to promote vascular healing. Methods: After implanting three types of DES in the coronary arteries of minipigs, we performed optical coherence tomography at weeks 2, 4, and 12 (n = 4, each). Afterward, we harvested the coronary arteries and performed immunofluorescence for endothelial cells (EC), smooth muscle cells (SMC), and nuclei. We obtained 3D stack images of the vessel wall and reconstructed the en-face view of the inner lumen. We compared re-endothelialization and associated factors among the different types of stents at different time points. Results: SES showed significantly faster and denser re-endothelialization than EES and BES at weeks 2 and 12. Especially in week 2, SES elicited the fastest SMC coverage and greater neointimal cross-sectional area compared to EES and BES. A strong correlation between re-endothelialization and SMC coverage was observed in week 2. However, the three stents did not show any difference at week 4 and week 12 in SMC coverage and neointimal cross-sectional area. At weeks 2 and 4, SMC layer morphology showed a significant difference by stents. A sparse SMC layer was associated with denser re-endothelialization and was significantly higher in SES. Unlike the sparse SMC layer, the dense SMC layer did not promote re-endothelialization during the study period. Conclusions: Re-endothelialization after stent implantation was related to SMC coverage and SMC layer differentiation. Further investigation is needed to explore methods for increasing the sparse SMC layer, to improve stent design and enhance both safety and efficacy.